A Brief History of Packaging - Kenneth R. Berger (EDIS)
For each product's needs, there are good packaging solutions. Though packages are often taken for granted, they are the result of many years of innovation -- in some cases accidental. A brief review of the more popular packaging developments are included in this fact sheet. This document is ABE321, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2002. Reviewed December 2005.